Migrants' and refugees' health status and healthcare in Europe: a scoping literature review - Adele Lebano; Sarah Hamed; Hannah Bradby; Alejandro Gil-Salmerón; Estrella Durá-Ferrandis; Jorge Garcés-Ferrer; Fabienne Azzedine; Elena Riza; Pania Karnaki; Dina Zota; Athena Linos (BMC, 2020)
Abstract Background There is increasing attention paid to the arrival of migrants from outwith the EU region to the European countries. Healthcare that is universally and equably accessible needs to be provided for these migrants throughout the range of national contexts and in response to complex and evolving individual needs. It is important to look at the evidence available on provision and access to healthcare for migrants to identify barriers to accessing healthcare and better plan necessary changes. Methods This review scoped 77 papers from nine European countries (Austria, Cyprus, France, Germany, Greece, Italy, Malta, Spain, and Sweden) in English and in country-specific languages in order to provide an overview of migrants' access to healthcare. The review aims at identifying what is known about access to healthcare as well as healthcare use of migrants and refugees in the EU member states. The evidence included documents from 2011 onwards. Results The literature reviewed confirms that despite the aspiration to ensure equality of access to healthcare, there is evidence of persistent inequalities between migrants and non-migrants in access to healthcare services. The evidence shows unmet healthcare needs, especially when it comes to mental and dental health as well as the existence of legal barriers in accessing healthcare. Language and communication barriers, overuse of emergency services and underuse of primary healthcare services as well as discrimination are described. Conclusions The European situation concerning migrants' and refugees' health status and access to healthcare is heterogeneous and it is difficult to compare and draw any firm conclusions due to the scant evidence. Different diseases are prioritised by different countries, although these priorities do not always correspond to the expressed needs or priorities of the migrants. Mental healthcare, preventive care (immunization) and long-term care in the presence of a growing migrant older population are identified as priorities that deserve greater attention. There is a need to improve the existing data on migrants' health status, needs and access to healthcare to be able to tailor care to the needs of migrants. To conduct research that highlights migrants' own views on their health and barriers to access to healthcare is key.